Older adults in forensic settings - Prescott, Dana (Handbook of forensic social work, 2024)
The chapters author begins by providing an overview of key demographics and host environments relative to social work practice with older adults in forensic settings. Next, an application of the National Association of Social Workers Code of Ethics lays the groundwork for understanding contemporary issues in forensic practice with older adults. The author then describes three central challenges, which include competency and capacity, criminal responsibility and sentencing mitigation, and child custody and protection. In addition to their description, the challenges include fields of practice involved and tips for navigating the challenge. The author closes the chapter with reflections on the populations and practice settings.